(untitled) (Conversatoria Linguistica, 2019)
Impaired hearing people suffer from a limited access to language system knowledge. Frequently, they do not master the language to the extend as to enable them to fully participate in the language communication process. In this paper we demonstrate our tests results on ways of words definitions presentation by impaired hearing people.